Professionalism Sustainable Development/Continuing professionality Development (CPD) Master Certified Teachers in SMK Rumpun Teknologi in Malang - Sujianto Sujianto (Pascasarjana Universitas Negeri Malang (UM), 2013)
Pengembangan Profesionalitas Berkelanjutan/Continuing Professionality Development (CPD) Guru Bersertifikat Pendidik di SMK Rumpun Teknologi se-Malang Raya Abstract: The purpose of this study is to describe the ongoing professional development of teachers as certified educators through self-development investment, scientific publications, and innovative work both independently, in groups, or institutionalized. This research uses descriptive quantitative research design, the research subjects are the certified vocational teacher educators in Malang. The research instrument used was a questionnaire sheet in the form of questionnaires and interview guidelines. These results indicate the fact that the implementation of Teachers and Lecturers Law (Law No. 14 of 2005), followed by professional allowance actually gives great hope to enthuse teachers to always develop professionalism, but the reality is not so. Continuous professional development of teachers are certified educators in SMK Rumpun Teknologi in Malang is still low, meaning that the majority of teachers are certified educators only in the category sometimes to do self-development investment, scientific publications, and create innovative work both independently, in groups, or institutional. Key Words: continuing professional development, self-development investment, scientific publications, innovative work Abstrak: Tujuan penelitian ini untuk mendeskripsikan pengembangan profesionalitas berkelanjutan guru bersertifikat pendidik melalui investasi pengembangan diri, publikasi ilmiah, dan karya inovatif baik secara mandiri, berkelompok, atau melembaga. Penelitian ini menggunakan rancangan penelitian deskriptif kuantitatif, dengan subjek penelitian guru kejuruan yang bersertifikat pendidik se-Malang Raya. Instrumen penelitian yang digunakan adalah lembar kuesioner yang berupa angket dan pedoman wawancara. Hasil penelitian ini menunjukkan kenyataan bahwa pemberlakuan UU Guru dan Dosen (UU Nomor 14 Tahun 2005) diikuti dengan tunjangan profesi sebenarnya memberikan harapan besar untuk menumbuhkan minat guru untuk selalu mengembangkan profesionalitasnya, namun kenyataannya tidak demikian. Pengembangan profesionalitas berkelanjutan guru bersertifikat pendidik di SMK rumpun teknologi se-Malang Raya masih tergolong rendah, artinya sebagian besar guru bersertifikat pendidik hanya dalam kategori kadang-kadang melakukan investasi pengembangan diri, publikasi ilmiah, dan membuat karya inovatif baik secara mandiri, berkelompok, atau melembaga.Kata kunci: pengembangan profesionalitas berkelanjutan, investasi pengembangan diri, publikasi ilmiah, karya inovatif